Evaluation of split cord malformation between years 2006 and 2020: A case series study - Mohammad Hassanzadeh; Khodakaram Rastegar; Mehrdad Hedayatizadeh; Pooria Rooyan (Elsevier, 2023)
Background: Split spinal cord malformation (SCM) is a rare congenital disorder leading to the split of the spinal cord by a bony or fibrous septum. Objectives: In the current study, we aimed to evaluate the patients with SCM who underwent surgery between 2006 and 2020. Methods: In this case series, thirty-five patients with SCM who underwent septal resection or spinal cord release surgery were enrolled and evaluated for type and site of the septum, accompanying some anomalies, such as neurological abnormalities, spinal deformities, and skin lesions. Also, the changes of neurological symptoms after surgery were securitized. Results: Thirty-five patients, including 27 females and 8 males, have been investigated. Scoliosis and Tethered cord syndrome were the most prevalent anomalies in 24 and 26 patients, respectively. The most common skin lesion was focal hirsutism in 14 patients, and the most common neurological disorder was the reduced muscle force observed in 5 patients, which was improved in two cases following surgeries. Conclusion: SCM occurred more frequently in females in comparison with males (77.14% in females and 22.85% in males). Scoliosis and Tethered cord syndrome were two dominant accompanying disorders with SCM. Moreover, focal hirsutism and reduced muscle force were the most common skin lesion and neurological disorders, respectively in these patients, respectively.